2020
DOI: 10.3390/vaccines8020164
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Emerging Genomic Landscape of CXCR4 in Cancer: A Lesson from WHIM

Abstract: Deciphering the molecular alterations leading to disease initiation and progression is currently crucial to identify the most relevant targets for precision therapy in cancer patients. Cancers express a complex chemokine network influencing leucocyte infiltration and angiogenesis. Moreover, malignant cells also express a selective repertoire of chemokine receptors that sustain their growth and spread. At present, different cancer types have been shown to overexpress C-X-C chemokine receptor type 4 (CXCR4) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 172 publications
(240 reference statements)
1
11
0
Order By: Relevance
“…These somatic mutations are primarily subclonal, and almost always associated with the MYD88 L265P mutation, the first identified recurring mutation in almost 67-90% of non-IgM secreting WM patients [6]. All 17 CXCR4 heterozygous mutations identified so far in WM span in the C-ter of the receptor, and closely resemble the already documented germline mutations of CXCR4 C-ter occurring in heterozygosis in WHIM syndrome [9]. Although their relevance for clinical presentation and overall survival, as well as their relationship with resistance to chemotherapy are still unsolved issues [26][27][28], several studies reported that patients with CXCR4 mutations present a significantly lower rate of adenopathy, and those with CXCR4 nonsense mutations have an increased BM disease burden, serum IgM levels, and/or risk of symptomatic hyperviscosity [29].…”
Section: Waldenstrom's Macroglobulinaemiasupporting
confidence: 53%
See 4 more Smart Citations
“…These somatic mutations are primarily subclonal, and almost always associated with the MYD88 L265P mutation, the first identified recurring mutation in almost 67-90% of non-IgM secreting WM patients [6]. All 17 CXCR4 heterozygous mutations identified so far in WM span in the C-ter of the receptor, and closely resemble the already documented germline mutations of CXCR4 C-ter occurring in heterozygosis in WHIM syndrome [9]. Although their relevance for clinical presentation and overall survival, as well as their relationship with resistance to chemotherapy are still unsolved issues [26][27][28], several studies reported that patients with CXCR4 mutations present a significantly lower rate of adenopathy, and those with CXCR4 nonsense mutations have an increased BM disease burden, serum IgM levels, and/or risk of symptomatic hyperviscosity [29].…”
Section: Waldenstrom's Macroglobulinaemiasupporting
confidence: 53%
“…At least 20 different WHIM/WHIM-like mutations have been described so far in the genomic region of chromosome 2q21 that encodes the C-ter of CXCR4 [9,29] (Figure 1). Interestingly, these mutations occur in the context of a gene that is highly conserved across species and span in a genomic region that is even more highly conserved than the gene as a whole [32].…”
Section: Genetic Barcode Of Whim Mutationsmentioning
confidence: 99%
See 3 more Smart Citations